Dieting reverses histone methylation and hypothalamic AgRP regulation in obese rats - Rapps, Kayla; Kisliouk, Tatiana; Marco, Asaf; Weller, Aron; Meiri, Noam (Frontiers in Endocrinology, 2023)
Although dieting is a key factor in improving physiological functions associated with obesity, the role by which histone methylation modulates satiety/hunger regulation of the hypothalamus through weight loss remains largely elusive. Canonically, H3K9me2 is a transcriptional repressive post-translational epigenetic modification that is involved in obesity, however, its role in the hypothalamic arcuate nucleus (ARC) has not been thoroughly explored. In the present study, we used a rodent model of diet-induced obesity (DIO) to assess whether histone methylation malprogramming impairs energy balance control and how caloric restriction may reverse this phenotype. Here we report that KDM4D, a specific demethylase of residue H3K9, plays a critical role in energy balance by directly modulating the expression of AgRP, a key neuropeptide that regulates hunger response. In DIO, downregulation of Kdm4d mRNA results in both enrichment of H3K9me2 on the AgRP promoter and transcriptional repression of AgRP. Because epigenetic modifications are dynamic, it is possible for some of these modifications to be reversed when external cues are altered. The reversal phenomenon was observed in calorically restricted rats, in which upregulation of Kdm4d mRNA resulted in demethylation of H3K9 on the AgRP promoter and transcriptional increase of AgRP. In order to verify that KDM4D is necessary to reverse obesity by dieting, we demonstrate that in vivo inhibition of KDM4D activity by pharmacological agent JIB-04 in naïve rats resulted in transcriptional repression of AgRP, decreasing orexigenic signaling, thus inhibiting hunger. We propose that the action of KDM4D through the demethylation of H3K9 is critical in maintaining a stable epigenetic landscape of the AgRP promoter, and may offer a target to develop new treatments for obesity.